What (if any) aesthetics of everyday experience should we have? - Angela Black (Aesthetic Investigations)
In this paper, I will show that an aesthetics of everyday experience independent of our analyses of art is absolutely essential. While the aims of discourse about art may be normative, the aims of discourse about everyday aesthetic experience are very different --- such discourse has, in part, epistemic goals, and, to the extent that it has a normative goal, such a goal is not agreement about the judgments of such experiences but about how disparate judgments can both find place in the shared aesthetic space. In other words, discourse about quotidian aesthetic experience is meta-aesthetic in character.